A Theory of the Currency Denomination of International Trade - Philippe Bacchetta; Eric van Wincoop (Swiss National Bank, Study Center Gerzensee, 2001)
Nominal rigidities due to menu costs have become a standard element in closed economy macroeconomic modeling. The "New Open Economy Macroeconomics" literature has investigated the implications of nominal rigidities in an open economy context and found that the currency in which prices are set has significant implications for exchange rate pass-through to import prices, the level of trade and net capital flows, and optimal monetary and exchange rate policy. While the literature has exogenously assumed in which currencies goods are priced, in this paper we solve for the equilibrium optimal pricing strategies of firms. We find that the higher the market share of an exporting country in an industry, and the more differentiated its goods, the more likely its exporters will price in the exporter's currency. Country size and the cyclicality of real wages play a role as well, but are empirically less important. We also show that when a set of countries forms a monetary union, the new currency is likely to be used more extensively in trade than the sum of the currencies it replaces.
Keywords: 330; Währung; Außenhandel; Außenhandelspreis; Marktanteil; Produktdifferenzierung; Offene Volkswirtschaft; Theorie